Luminescence properties of a novel promising red phosphor Na3Gd2−x(BO3)3:xEu3+. (November 2016) - Wei, Tengyue; Ren, Qiang; Wu, Xiulan; Shi, Xiaolei; Wang, Baoxing; Huo, Zhezhe
Abstract: The novel red-emitting Na3 Gd2− x (BO3 )3 : x Eu 3+ phosphors were synthesized by a solid-state method. Under near ultraviolet excitation, the phosphors exhibit dominant emission peak at 614 nm and generate bright red light, which is attributed to the electric-dipole transition 5 D0 → 7 F2 . The optimal doping amount of Eu 3+ in Na3 Gd2− x (BO3 )3 : x Eu 3+ phosphors is x =0.3 for the maximum emission. The exchange interaction between Eu 3+ ions is identified to be the main mechanism in the concentration quenching process. The CIE color coordinates of the Na3 Gd2− x (BO3 )3 : x Eu 3+ phosphors (x=0.650, y=0.350) are close to the NTSC standard values of red. With a relatively high quantum efficiency of 35.2%, Na3 Gd2 − x (BO3 )3 : x Eu 3+ red-emitting phosphor is probably a promising candidate for near ultraviolet-based white LEDs application. Highlights: A new promising red-emitting Na3 Gd2 (BO3 )3 :Eu 3+ phosphor was synthesized. The microstructure and properties of the phosphor were researched in detail. The phosphor can exhibit pure red light under near-UV excitation. The quantum efficiency of Na3 Gd2 (BO3 )3 :Eu 3+ phosphor is as high as 35.2%.